THU0174 Endothelial microparticles and circulating endothelial progenitor cells in primary sjægren's syndrome patients: A potential marker of endothelial damage?. (23rd January 2014) - Bartoloni, E.; Alunno, A.; Pirro, M.; Bistoni, O.; Schillaci, G.; Bagaglia, F.; Luccioli, F.; Santoboni, G.; Mirabelli, G.; Cannarile, F.; Mannarino, E.; Gerli, R.
Abstract : Background: Patients with systemic inflammatory and autoimmune diseases display an increased risk of cardiovascular (CV) mortality. Inflammatory and immune-mediated mechanisms have been identified to promote induction and progression of atherosclerotic endothelial injury (1). Sjögren's syndrome (SS) represents an interesting model to investigate pathogenetic mechanisms involved in atherosclerotic damage. Young SS patients are characterized by an accelerated subclinical atherosclerotic damage and disease-related immune mechanisms may be involved in this process (2, 3). However, the exact pathogenetic mechanisms involved in the precocious vascular damage in SS are still unknown. Recent evidence suggests that endothelial integrity loss may involve defects in the vascular regenerative capacity provided by circulating endothelial progenitor cells (EPC) and generation of circulating microparticles (MPs). Endothelial (E) MPs represent an emerging marker of endothelial dysfunction in patients with CV diseases and an increased number of EMPs have been demonstrated in diseases characterized by high inflammatory response, as polymyalgia rheumatica (4). Increased levels of leukocyte and platelet MPs have been recently demonstrated in SS and have been identified as biomarkers reflecting systemic cell activation. On the other hand, the role of EMPs in SS has never been investigated. Objectives: Evaluate the degree of endothelial injury in SS patients by measuring number of circulating EMPs and their repair potential by EPC measurement. Methods: 31 SS patients (30 female, 1 male, mean age 52±12 SD) and 31 age- and sex-matched normal controls (NC) were enrolled. Number of circulating EMPs (CD31+/CD42-) and EPC (CD34+/KDR+) was quantified by FACS analysis. Parameters of disease activity and damage were measured by ESSDAI (inactive ≤2, active >2) and SSDDI, respectively. Disease-related clinical features, laboratory markers of immunologic dysfunction and traditional CV risk factors were recorded. Results: SS patients displayed higher levels of EMPs and lower count of EPC than NC (634±21548 vs 399±28 n/microL: p<0.001 and 203±16 vs 563±21 n/mL: p<0.001, respectively). No correlation was depicted between EMPs, EPCs and EMP/EPC ratio and parameters of disease activity/damage or disease-related clinical and immunologic features. Of interest, a correlation was demonstrated between number of cigarettes smoked and active disease (p=0.001). Conclusions: This is the first demonstration of a significant imbalance between endothelial injury and repair in SS, as demonstrated by increased number of EMPs associated with EPC count reduction. In this setting, increased endothelial fragmentation in association with a reduced endothelial repair may advocated as adjunctive potential pathogenic mechanism promoting subclinical atherosclerotic damage in SS. Among traditional CV risk factors, smoke may be associated with an higher risk of active disease. References: Bartoloni E et al. Arthritis Care Res 2011;63:178 Vaudo G et al. Arthritis Rheum 2005;52:3890 Gerli R et al. Arthritis Care Res 2010;62:712 Pirro M et al. J Intern Med 2011 [Epub ahead of print] Disclosure of Interest: None Declared